Redesign of venting machine to reduce scrap defect crease in tires manufacture company - Fajar Abdul Aziz; Subekti Subekti (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2024)
An apparatus for venting or perforating green tires in order to release trapped air is known as a-venting machine. Productivity will drop in May and July of 2023 as a result of scrap issues brought on by green tire defect creases. The term